INFLUENCE OF LEADERSHIP IN RURAL COMMUNITY DEVELOPMENT IN THE STATE OF TERENGGANU, MALAYSIA - Rami, Ahmad Aizuddin Md; Abdullah, Ramle; Simin, Mohamad Hafis Amat (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Challenges in rural communities call for awareness of community leaders in overcoming these challenges. One of these challenges is the governmentâs endeavour to ensure that the rural community development is parallel to the countryâs development; hence, a credible, effective community leader is needed to achieve the countryâs development aspiration. This study was conducted in four rural communitiesin the state of Terengganu, Malaysia to identify the role played by local community leaders. These communities were selected based on their excellent achievement in community development programmes and contests. The objectives of this research are, (1) identifying the role of leaders in bringing success for every development programme and (2) ascertaining the leadership style that can bring positively impact a community. The data for this study were obtained from observations and interviews with 40 respondents who comprised of chairpersons and members of the Villages Development and Safety Committee (J3K), as well as local residents. The findings showed that effective community leadership plays a significant role as an agent of change and has the ability to positively impact the development of rural community. Besides that, community leadersâ practise of effective leadership style is perceived to bring changes among the community in the social, economic and cultural aspects, as well as changes in the way of thinking among rural communities. In this regard, leadership in these four communities is viewed to manifests the change into better leadership that can inspire other community leaders.